MENINGKATKAN MOTIVASI BELAJAR DENGAN MODEL TALKING STIK WITH MUSIC DI SD NEGERI JANTI SLAHUNG PONOROGO - Lilis Sumaryanti (AL-ASASIYYA: Journal Of Basic Education, 2017)
The duty of an educator is giving a knowledge to their students, train a skill, as well as to determine direction and belief. In implementing the tasks and this requirement so an educator must have patience, creativity, be an example and had to have basic knowledge in teaching, belong applies the methods of truth and a proper.Therefore, the use of the proper model is also necessary for The elementary school subdistrict Slahung, district Ponorogo, learning the Indonesian language his ability to read technical use the model talking stick with music a student of The elementary school subdistrict Slahung, district Ponorogo years lessons 2016/2017 increase.The increase was shown as follows: (1) in cycle 1 first meeting motivation ( interest ), the role of and liveliness students in reading technical increased than before use the model talking stick with music , are still less maximally because the outcomes learning still about 60 % , (2) cycle 1 the second lessons students have somewhat increased to 70 % , (3) cycle 2 and sub-basic subjects of different from the round first and second but still use the model talking stick with music in Learning so interest, the role of and liveliness students in reading technical in and teaching process increase with the outcomes learning around 80 % .This proves that model talking stick with music acceptably well by students because in it contains elements learning while playing